MASALAH DAN TANTANGAN PRIVATISASI PENDIDIKAN TINGGI - Nurika Khalila Daulay (UIN Sumatera Utara Medan, 2014)
The privatization of higher education is often understood as the commercialization of education, where higher education turned into a business area that applies economic principles